PERMASALAHAN YANG DIHADAPI SINGLE PARENT DI JORONG KANDANG HARIMAU KENAGARIAN SIJUNJUNG DAN IMPLIKASINYA TERHADAP LAYANAN KONSELING - Mailany, Irma (Universitas Negeri Padang, 2013)
Single parent has a dual role as a parent to his children. This study aimed to describe the problems faced by single parent in their personal, social, family, work and religion life. Subjects were 40 widows. The research findings indicate that single parent who caused the divorce with husband having problems about relations with the husband's family, while single parent caused by the death of her husband having problems in terms of physical condition, health, and finances. Â Keywords: Problems, Single Parent.